Commodification of the Qur'an as an Advertising Strategy for Women's Clothing in the @hijabalila Account - Jannah, Roudlotul (Universitas Nurul Jadid, 2023)
The Qur'ān that is present in social media by involving meaning tends to lead to commodification efforts. The @hijabalila account as a Muslim women's clothing sales account uses the meaning of the Qur'ān as a means of advertising its commodities. The meaning made by the @hijabalila account is adjusted to marketing interests by using language narratives. The adjustment of meaning to the marketing interests of the @hijabalila account ignores other forms of meaning of the criteria for women's clothing which has an impact on changing the function of the Quran as a commodification tool. So, this research focuses on examining how the process of commodification of the Quran is used as an advertisement for women's clothing on the @hijabalila account. This research was applied using a qualitative method of literature review obtained from data sources related to research with the theory of Vincent Mosco's political economy approach. As a result, the commodification process carried out by the @hijabalila account can be seen from three sides. First, the @hijabalila account gives meaning to the Qur'an adjusted to the goods sold and used as content. Second, besides utilising the interpretation of the Qur'an to attract audiences, the @hijabalila account also uses Isntagram as a medium for marketing expansion. Third, there is a process of production and reproduction through the formation of meaning in the verses of women's clothing by the @hijabalila account to the audience.